Safety effect of fractions from methanolic leaf extract of Ocimum gratissimum on reproduction in male wistar rats - Njan, Anoka A. (Toxicol Rep, 2019)
This study evaluates the reproductive toxicity of ethyl acetate and butanolic fractions from crude methanolic leaf extract of Ocimum gratissimum in male Wistar rats. Acute toxicity was assessed to determine the safety dose, Sub-chronic reproductive toxicity studies were carried out by administering daily 25, 100 and 400 mg/kg body weight doses of the fractions to respective group of animals and 1 ml of normal saline daily for the control group for 28 days. Blood, epididymis and testes were harvested for reproductive hormones, sperm parameters, and histopathologic analysis respectively. There was significant (P < 0.05) increase in serum levels of testosterone, body-weight gain, sperm count. There was also apparent increase in mean-testicular weight and preservation of testicular histology with increase spermatogenesis in both the ethyl acetate and butanolic fraction treated groups compared with control. Serum levels of luteinising hormone was however significantly (P < 0.05) decrease across the groups compared to control. These effects were more pronounced in the butanolic fraction group compared to the ethyl acetate treated group. Sperm motility was also significantly (P < 0.05) higher in the ethyl acetate treated group compared to control. Findings from this studies demonstrate that these fractions were non-toxic at the tested doses with regards to male reproduction but, rather, exhibited fertility enhancing effects which was better with the butanolic fraction. Our findings also shows that the ethyl acetate fraction may be safer than the butanolic fraction.